Dermatoglyphics and schizophrenia : analysis of quantitative traits - Turek, Stjepan (Array, 1990)
Quantitative dermatoglyphic traits of the digito-palmar complex were analyzed in a group of 195 male and 115 female patients suffering from chronic schizophrenia, and were compared to a control group of 200 male and 200 female phenotypically healthy persons. Statistically significant differences were found in both sexes between the two groups, and palmar traits are shown to be strong discriminators between the two groups, with a correct classification of over 80% of all subjects